MATRIMONIAL MARKET DYNAMICS IN KERALA: A CRITICAL INVESTIGATION OF THE ADVANCEMENT OF MATRIMONIAL ADVERTISEMENTS IN KERALA - Sarath Krishna A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Marriage, as a social institution is prevalent in the cultural landscape of Kerala. The cultural diversity of Kerala can be observed from its heterogeneity in customs, rituals and practices. ‘Arranged marriages’ are the traditional and most common kind of marriage that happen in Kerala. These marriages are generally facilitated through matrimonial advertisements which commodify the institution of marriage itself. They also serve as spaces of segregation on the basis of religion, caste, class and gender. The normalisation of conventions takes place through such advertisements which is being catered to the general public through newspapers, matrimonial websites, television channels and social media platforms. It seems that even the tastes and important life choices of individuals are shaped on the terms dictated by the culture industry. The paper studies the evolution of matrimonial advertisements with respect to the sociocultural transformations that happened in the Kerala society. The study aims to analyse the process of evolution from the era of marriage brokers and marriage bureaus to the era of social media and dating platforms. It also identifies the point of rupture in this evolutionary process which can be considered as a harbinger of progressive change in the sociocultural landscape of Kerala.